Mathematics
AlisiaDiepenbrock
41

Solve the system of equations using substitution. 3x + 2y = 7 y = –3x + 11

+4
(1) Answers
rekeyia21

3x + 2y = 7 y = -3x + 11 Solve the system of equation using substitution. Substitute the y in the first equation by its value presented in the 2nd equation. 3x + 2y = 7 3x + 2(-3x + 11) = 7 3x - 6x + 22 = 7 -3x + 22 = 7 -3x = 7 - 22 -3x = -15 -3x/-3 = -15/-3 x = 5 Substitute x in the 2nd equation by its computed value. x = 5 y = -3x + 11 y = -3(5) + 11 y = -15 + 11 y = -4 x = 5 ; y = -4 Substitute x and y in the 1st equation with its corresponding values 3x + 2y = 7 3(5) + 2(-4) = 7 15 - 8 = 7 7 = 7

Add answer